2004
DOI: 10.1073/pnas.0400541101
|View full text |Cite
|
Sign up to set email alerts
|

Reinitiation involving upstream ORFs regulates ATF4 mRNA translation in mammalian cells

Abstract: During cellular stresses, phosphorylation of eukaryotic initiation factor-2 (eIF2) elicits gene expression designed to ameliorate the underlying cellular disturbance. Central to this stress response is the transcriptional regulator activating transcription factor, ATF4. Here we describe the mechanism regulating ATF4 expression involving the differential contribution of two upstream ORFs (uORFs) in the 5 leader of the mouse ATF4 mRNA. The 5 proximal uORF1 is a positive-acting element that facilitates ribosome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
1,392
4
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,491 publications
(1,447 citation statements)
references
References 27 publications
43
1,392
4
8
Order By: Relevance
“…This mechanism is also used in the expression control of some important regulatory genes. (48)(49)(50)(51)(52)(53) For example, the mRNA of transcriptional factor SCL contains four start codons preceded by small uORF. It was demonstrated that ribosomes reach the first SCL start codon mostly by leaky scanning (skipping the uORF start codon), but the other three protein isoforms are synthesized by ribosomes reinitiating translation after termination at stop codon of uORF.…”
Section: Types Of Alternative Open Reading Framesmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is also used in the expression control of some important regulatory genes. (48)(49)(50)(51)(52)(53) For example, the mRNA of transcriptional factor SCL contains four start codons preceded by small uORF. It was demonstrated that ribosomes reach the first SCL start codon mostly by leaky scanning (skipping the uORF start codon), but the other three protein isoforms are synthesized by ribosomes reinitiating translation after termination at stop codon of uORF.…”
Section: Types Of Alternative Open Reading Framesmentioning
confidence: 99%
“…(54) This mechanism links the expression control of some important regulatory factors with cellular response to stress conditions through the eIF2 phosphorylation. (50,55) Thus, it seems likely that the low synthesis rate of some eukaryotic proteins is an important characteristic of their gene expression patterns. However, the regulatory role of uORFs in the selection of translation start sites is commonly not taken into account in gene annotation procedures.…”
Section: Types Of Alternative Open Reading Framesmentioning
confidence: 99%
“…p53 isoforms gain functions V Olivares-Illana and R Fåhraeus suppress cap-dependent translation, but will also allow cap-independent translation to take place in a selected number of mRNAs, such as ATF4 and cat-1, and IREScarrying mRNAs, such as p58 PITSLRE (Cornelis et al, 2000;Fernandez et al, 2002;Vattem and Wek, 2004). Interestingly, the latter shows similarities in mRNA translation control to p53 and p53/47 as the IRES of p58 PITSLRE is within the coding sequence of p110 PITSLRE .…”
Section: Introductionmentioning
confidence: 99%
“…ATF4 is a transcription factor that initiates a crucial response during the UPR, being responsible for the activation of a large set of genes important for recovery and tolerance to ER and oxidative stress (39). Selective translation of ATF4 results from the presence of two conserved uORFs in its 5 ¶ UTR (100,101). uORFs act as a barrier to translation of the correct ORF because ribosome initiation at the start codon of the uORF prevents the ribosome from reaching the correct start codon.…”
Section: Selective Gene Expression Mediated By Eif2 Regulation Duringmentioning
confidence: 99%